Impact of Personality Trait of Agreeableness on Oral Parafunctional Habits - Afsar, Ruhab; Shoaib, Laiba; Haider, Arslan; Liaqat, Samra; Butt, Hira; Khan, Nauman Rauf; Jabbar, Maria (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To find the impact of agreeable personality trait on oral parafunctional habits. METHODOLOGY A Cross-sectional descriptive study was conducted at the College of Dentistry, Sharif Medical and Dental College, Lahore, over 5 months, from July to November 2021. Data was collected using medical questionnaire and ten item personality inventory scale (TIPI). Kruskal Wallis test was to find the difference in the scores of agreeable personality trait across groups of oral parafunctional habits. RESULTS There was a statistically significant difference in the agreeable personality trait across the parafunctional habits of tooth grinding (p=0.023) and biting on hard objects (p=0.013). A non-significant difference was seen in the personality trait across the habits of nail biting (p=0.495), tooth clenching (p=0.097) and habit of chewing gum (p=0.371). CONCLUSION The individuals who disagreed to having the habit of tooth grinding had the highest score for agreeableness and the least was seen in those who neither agreed nor disagreed to having the habit. The personality trait was the most prevalent in individuals who strongly agreed to having the habit of biting on hard objects and the least in those who agreed to having the habit.